Pengaruh Metode Problem Posing terhadap Berpikir Kritis dalam Pembelajaran Pendidikan Agama Kristen Siswa Kelas X SMA PGRI Siborongborong - Yuri Anty Br. Sianturi (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2021)
ABSTRACT                The purpose of this study is to experience the positive and significant influence of the use of Problem Posing Methods on Critical Thinking during the Learning PAK Students Class X SMA PGRI Siborongborong 2020/2021 Learning Year. The methods used are quantitative methods. The population of students in class X SMA PGRI Siborongborong approximately 392 people and a sample taken from the 22% the number of 86 people. Data were collected with a positive closed questionnaire into 33 items. The results of the data analysis showed that there was a positive and significant effect of the Positive Problem Method on Critical Thinking in PAK Learning as evidenced by the analytical data: a) positive correlation test found rxy value = 0.364 rtabel (a = 0.05, n = 86) = 0.213. b) Significant relationship test obtained calculation value = 3,583 ttable (a = 0.05, dk = n-2 = 84) = 2,000. c) Regression of the equation. d) Regression determination (r2) = 13.3% thus H0 is rejected and Ha is accepted.Keywords: Problem Posing Method, Critical Thinking